Molten salt assisted synthesis of black titania hexagonal nanosheets with tuneable phase composition and morphology1. Issue 104 (11th November 2015) - Xu, Jijian; Zhu, Guilian; Lin, Tianquan; Hong, Zhanglian; Wang, Juan; Huang, Fuqiang
<x xml:space="preserve">Abstract</x> A facile high yield molten salt route to fabricate black titania hexagonal nanosheets under atmospheric pressure and low temperature.